Genetic Gain and Heritability of Seedling Characters Selected at a Low Temperature in Pearl Millet (Pennisetum typhoideum Rich.) - Totok Agung Dwi Haryanto; Tae-Kwon Shon; Tomohiko Yoshida (Plant Production Science, 1998)
One cycle of selection was applied for studying genetic gain and heritability of seedling characters such as shoot length and root length at a low temperature in two genetic populations. The correlation of these characters to yield components was also examined. Selection had a significant effect on seedling characters other than shoot-root ratio. Selection for a long shoot or root increased the percentage of germination, shoot length, root length, panicle length and panicle weight in the field. Shoot length was significantly correlated to root length. There was a relationship between seedling characters and yield components. A genetic gain for seedling characters was obtained. Shoot and root lengths are heritable characters and may be useful as selection criteria at low temperatures. Heritability differed with the population selected for shoot or root length. Heritability values were 0.28˜0.69 for shoot length and 0.37˜0.76 for root length. Further selection gain for a longer shoot and root should be possible.